1955
DOI: 10.1039/jr9550000773
|View full text |Cite
|
Sign up to set email alerts
|

The chemistry of silica surfaces

Abstract: Holt and Kiqzg. 773 The Chemistry of Silica Surfaces.By P. F. HOLT and D. T. KING.[Reprint Order No. 5820.1Solubility measurements indicate that an incomplete monolayer normally exists on silica surfaces which is more soluble than the rest of the material. This layer has been identified as silicic acid by following the exchange reaction between a quartz surface and dissolved p1Si]silicic acid. The layer is removed by sodium hydroxide and re-formed when the silica is equilibrated with a silicic acid solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

1958
1958
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 0 publications
2
15
0
1
Order By: Relevance
“…However, account has not been taken here of the considerable release of native silica from some clays. Holt and King (1955) reported sorption of .silicic acid on finely ground quartz at pH 8 but not at pH 4 and sorption of monosilicic acid on clay crystal faces cannot be ruled out. Further investigations are being carried out on this problem.…”
Section: Discussionmentioning
confidence: 74%
“…However, account has not been taken here of the considerable release of native silica from some clays. Holt and King (1955) reported sorption of .silicic acid on finely ground quartz at pH 8 but not at pH 4 and sorption of monosilicic acid on clay crystal faces cannot be ruled out. Further investigations are being carried out on this problem.…”
Section: Discussionmentioning
confidence: 74%
“…Holt and King (1955) have shown that silica surfaces usually carry an incomplete monolayer of silicic acid which can be removed only by preliminary treatment by sodium hydroxide. This surface layer dissolves rapidly and provides much of the silica found in the solution.…”
Section: Particle Size and Solubilitymentioning
confidence: 99%
“…Sua retenção, comprovada por Holt & King (1955) por meio do Si 31 (radioativo), ocorre por adsorção específica às superfícies dos óxidos de Fe, à semelhança do P (Hingston et al, 1972). Fósforo e silício competem entre si pelos mesmos sítios de adsorção, de maneira que o segundo pode deslocar (dessorver) o primeiro, e vice-versa, da fase sólida para a líquida (Obihara & Russel, 1972;Oliveira, 1984;Leite, 1997).…”
Section: Introductionunclassified